GAMBARAN STATUS LITERASI KESEHATAN IBU HAMIL DI PUSKESMAS TUMINTING MANADO [DESCRIPTION OF THE HEALTH LITERACY STATUS OF PREGNANT WOMEN IN TUMINTING HEALTH CENTER, MANADO] - Maria Lupita Nena Meo; Rina M Kundre; Hendro J Bidjuni (Universitas Pelita Harapan, 2023)
Maternal health literacy is one of the main factors affecting the health and well-being of mothers during pregnancy. Maternal health literacy status will affect the ability of pregnant women to obtain, understand and use basic information about health and make the right health decisions for themselves and their babies. Researchers have not found published studies regarding the health literacy status of pregnant women in Manado City. Therefore, this study aims to provide an overview of maternal health literacy in pregnant women in basic health facilities. This research is a quantitative study with a survey design conducted at one of the community health centers in Manado City. The number of respondents who participated in this study were 90 pregnant women who were recruited using simple random sampling technique. Data was collected using the Maternal health literacy inventory in pregnancy (MHELIP) and analyzed using descriptive analysis. The results showed that 31 respondents (35%) were in extraordinary literacy status, 30 respondents (33%) were in sufficient literacy status, 15 respondents (17%) were in problematic literacy status, and 13 respondents (15%) were in inadequate literacy status. The results of the study found that most of the mothers were in extraordinary literacy levels and moderate literacy status. However, there was no significant difference at each level of literacy status of pregnant women. Health service providers have an important role in improving the literacy status of pregnant women, because mothers with limited literacy status rely on health workers as a source of health information.BAHASA INDONESIA ABSTRAK Literasi kesehatan ibu merupakan salah satu faktor utama yang mempengaruhi kesehatan dan kesejateraan ibu selama kehamilan. Status literasi kesehatan ibu akan mempengarhi kemampuan ibu hamil untuk memperoleh, memahami dan menggunakan informasi dasar tentang kesehatan serta membuat keputusan kesehatan yang tepat untuk dirinya sendiri dan bayinya. Peneliti belum menemukan kajian terpublikasi mengenai status literasi kesehatan ibu hamil di Kota Manado. Oleh karena itu penelitian ini bertujuan untuk memberikan gambaran literasi kesehatan maternal pada ibu hamil di fasilitas kesehatan dasar Penelitian ini merupakan penelitian kuantitatif dengan desain survey yang dilakukan di salah satu puskemas di Kota Manado. Jumlah responden yang berpartisipasi dalam penelitian ini adalah 90 ibu hamil yang direkrut dengan menggunakan teknik simple random sampling. Data dikumpulkan menggunakan Maternal health literacy inventory in pregnancy (MHELIP) dan dianalisis menggunakan analisis deskritif. Hasil penelitian menunjukan bahwa 31 responden (35%) berada dalam status literasi luar biasa, 30 responden (33%) berada dalam status literasi cukup, 15 responden (17%) berada dalam status literasi bermasalah, serta 13 responden (15%) berada dalam status literasi tidak memadai. Hasil penelitian menemukan bahwa sebagian besar ibu berada dalam tingkat literasi luar biasa dan status literasi cukup. Akan tetapi tidak ada perbedaan yang signifikan di tiap tingkat status literasi ibu hamil. Penyedia layanan kesehatan memiliki peran penting dalam meningkatkan status literasi ibu hamil, karena ibu dengan status literasi terbatas mengandalkan tenaga kesehatan sebagai sumber informasi kesehatan